2006
DOI: 10.1021/nl060437q
|View full text |Cite
|
Sign up to set email alerts
|

Clean Carbon Nanotube Field Emitters Aligned Horizontally

Abstract: Horizontally aligned carbon nanotube (CNT) field emitters, which strongly adhere to the substrate and show good field emission properties, were fabricated by electrophoresis deposition and fissure formation techniques. A thin film of CNTs was deposited on a substrate, by electrophoresis, from an aqueous mixture of CNT and detergent, and then the detergent was deposited also by electropholysis. CNTs with a clean surface were exposed in the fissures produced by firing. The field emission was increased significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 26 publications
0
28
0
1
Order By: Relevance
“…Moreover, it is worth noting that the E to value of graphene films is significantly lower than those from Spindt-type Mo emitters [33] and wide-band-gap semiconducting materials, [6,[34][35][36][37][38][39] such as nanostructured diamond films, AlN, and LiF. The E to value of graphene films is also lower than that of free-standing sub-nanometer graphite sheets (E to, 4.7 V mm À1 ) synthesized by PECVD, [19] and the E to and E thr values are well comparable to those of CNT films fabricated by EPD (E to , 1.4-3.0 V mm À1 ) [28,29,40,41] and screen-printing (E to , 2-6.4 V mm À1 ) techniques. [42] The Fowler-Nordheim (F-N) theory is the most-commonly used model for understanding the electron emission from a metal surface under a strong applied field, and it has been also widely used to investigate the electron-emission behavior of various nanostructures, such as CNTs, [3][4][5][43][44][45] nanowires, [46] and nanowalls.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Moreover, it is worth noting that the E to value of graphene films is significantly lower than those from Spindt-type Mo emitters [33] and wide-band-gap semiconducting materials, [6,[34][35][36][37][38][39] such as nanostructured diamond films, AlN, and LiF. The E to value of graphene films is also lower than that of free-standing sub-nanometer graphite sheets (E to, 4.7 V mm À1 ) synthesized by PECVD, [19] and the E to and E thr values are well comparable to those of CNT films fabricated by EPD (E to , 1.4-3.0 V mm À1 ) [28,29,40,41] and screen-printing (E to , 2-6.4 V mm À1 ) techniques. [42] The Fowler-Nordheim (F-N) theory is the most-commonly used model for understanding the electron emission from a metal surface under a strong applied field, and it has been also widely used to investigate the electron-emission behavior of various nanostructures, such as CNTs, [3][4][5][43][44][45] nanowires, [46] and nanowalls.…”
mentioning
confidence: 81%
“…It should be emphasized here that, for a similar current density, our single-layer graphene film exhibits much better emission stability than single-walled-CNT (SWCNT) and multiwalled-CNT (MWCNT) films fabricated using the spray method, [48] EPD, or combination of EPD and other techniques, [29,41] and grown by the CVD process. [28] Previous studies [4] showed that the emission degradation is a factor of 10 faster for SWCNTs than for MWCNTs, because of the single shells of SWCNTs are more sensitive to ion bombardment and irradiation, while the multiple shells of MWCNTs tend to stabilize their structure.…”
Section: Ma CMmentioning
confidence: 99%
See 1 more Smart Citation
“…Jung et al 183,184 deposited a thin film of horizontally aligned SWCNTs from an aqueous mixture of CNT and detergent. The coating was naturally dried and then pressed on the surface to make it smooth.…”
Section: Epd Of Carbon Nanotubes (Cnts)mentioning
confidence: 99%
“…A transparent hard stamp of quartz glass [6] or soft elastomeric stamp (for instance PDMS) [7][8][9] is done the resin cured by UV-light exposure. However, it is of importance to fabricate the desired stamp in nanoimprint lithography process.…”
Section: Introductionmentioning
confidence: 99%